YELLOW SWEET POTATO STARCH HYDROLYSIS INTO GLUCOSE ENZYMATICALLY - Risnoyatiningsih, Sri (Jurnal Teknik Kimia, 2008)
Glucose is a monosaccharide found in many fruits, and plants obtained through a process using enzymehydrolysis of starch saccharide. Sweet potato starch Hydrolisis run with three neck flask equipped with astirrer. In Liquifikasi stage, three-neck flask is inserted into the starch solution which has been set temperatureand the pH was added HCI and in the heat, then added α-amylase enzyme in a certain time. Saccharification second stage, where the results liquification cooled, set the temperature and pH on certain conditions. Then added enzyme giukoamilase by volume according to the specified variable, and incubated at a given time. At acertain time interval was taken a few examples of the analyzed samples will be analyzed glucose levels Process behavior observed in this study were changes in temperature, hydrolysis time and the addition of enzymes, the best hydrolysis results obtained at 60 ° C, pH 4.5 and the addition of 0.7 ml of glucoamylase and time hydrolysis 5 days with glucose levels reaching 5 , 65% and conversion yield of 66.8% and 22.59%.Key words: Sweet Potato Starch, Liquificationi, saccharifictsion, glucose, α-amylase enzyme